Rendahnya Pemahaman Konsep Matematika Siswa Kelas V SDN 33 Kalumbuk - Melisa Asgustira (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Understanding of Mathematics concepts is an important factor in determining students' learning success. However, the results of observations at SDN 33 Kalumbuk showed that fifth grade students still had difficulty in understanding Mathematics concepts. This can be seen from the low level of learning completion, which was only 36.84% in class VA and 33% in class VB. The low understanding of concepts is caused by the lack of interactive learning methods, so that students get bored easily and are less involved in the learning process. This article discusses the importance of understanding concepts in Mathematics learning and solutions that can be applied to improve student understanding. One of the proposed strategies is the use of the Make a Match learning model, which can increase student engagement and help them understand concepts more concretely and interestingly. In addition, problem-solving approaches, the use of visual media, group discussions, and continuous evaluation can also be applied to improve learning effectiveness. By implementing innovative and interactive learning methods, it is hoped that students' understanding of Mathematics concepts can improve, so that they are better prepared to face academic challenges and are able to apply Mathematics concepts in everyday life.